Stereotactic radiofrequency amygdalohippocampectomy: does reduction of entorhinal and perirhinal cortices influence good clinical seizure outcome? - Malikova, Hana; Liscak, Roman; Vojtech, Zdeněk; Prochazka, Tomas; Vymazal, Josef; Vladyka, Vilibald; Druga, Rastislav (Epilepsia, 2011)
PURPOSE: Stereotactic radiofrequency amygdalohippocampectomy (SAHE) has been modified recently in our center for the therapy of mesial temporal epilepsy (MTLE). It has promising clinical results comparable with microsurgical amygdalohippocampectomy despite smaller volume reduction of the hippocampus. We hypothesized that the extent of perirhinal and entorhinal cortex (PRC, EC) reduction could explain the clinical outcome. Therefore, we performed, retrospectively, volumetric analysis of PRC and EC and compared it with the seizure control. METHODS: Twenty-six consecutive patients with MTLE treated by SAHE were included. PRC and EC volumes were measured from magnetic resonance imaging (MRI) records obtained before and 1 year after SAHE. The clinical outcome was assessed each year after SAHE using Engel's classification. KEY FINDINGS: Twenty-six patients were analyzed. The volume of PRC decreased by 46 ± 17% (p < 10(-12) ); EC volume decreased by 56 ± 20% (p < 10(-10) ). Two years after the procedure, 73% of patients were classified as Engel's I, 19% as Engel's II; in 2 (8%) the treatment failed (were reoperated). Eighteen patients finished 3 years follow-up; 72% of them were classified as Engel's I, 17% as Engel's II, and in 2 (11%) above-mentioned patients the treatment failed. Thirteen patients finished 4 years of follow-up, 11 of them as Engel's I. There was no significant correlation of the clinical outcome to PRC and EC volume reductions. SIGNIFICANCE: The clinical effect of SAHE is not clearly explained by the volume reductions of PRC and EC (nor of the hippocampus and the amygdala). It promotes opinion that the extent of resection/destruction is not important for seizure outcomes.
Keywords: Amygdala; Adolescent; Magnetic Resonance Imaging; Adult; Male; lidé; mapování mozku; Treatment Outcome; Brain Mapping; lidé středního věku; Humans; Epilepsy, Temporal Lobe; Middle Aged; Electrocoagulation; Hippocampus; Entorhinal Cortex; epilepsie temporálního laloku; elektrokoagulace; hipokampus; mužské pohlaví; výsledek terapie; Radiosurgery; radiochirurgie; dospělí; cortex entorhinalis; amygdala; ženské pohlaví; mladiství; Female; magnetická rezonanční tomografie